2022
DOI: 10.1021/acsomega.1c04416
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Water Saturation in Tight Gas Sandstone Formation Using Artificial Intelligence

Abstract: Water saturation ( S w ) is a vital factor for the original oil and gas in place (OOIP and OGIP). Numerous available equations can be used to calculate S w , but their values have been unreliable and strongly depend on core analyses, which are costly and time-consuming. Hence, this study implements artificial intelligence (AI) modules to predict S w from the conventional well logs. Artificial neural netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Both models achieved accurate Sw estimation with R values exceeding 0.90 and AAPE less than 5%. The study introduced a new empirical correlation derived from ANN biases and weights, validated with unseen data, providing a reliable method for Sw prediction without costly core analyses 42 . Markovic and colleagues (2022) conducted a thorough examination using the XGBoost technique to ascertain inter-pore SW within Canadian sandstone oil resources through the analysis of LF-NMR and density information 43 .…”
Section: Research Backgroundmentioning
confidence: 99%
“…Both models achieved accurate Sw estimation with R values exceeding 0.90 and AAPE less than 5%. The study introduced a new empirical correlation derived from ANN biases and weights, validated with unseen data, providing a reliable method for Sw prediction without costly core analyses 42 . Markovic and colleagues (2022) conducted a thorough examination using the XGBoost technique to ascertain inter-pore SW within Canadian sandstone oil resources through the analysis of LF-NMR and density information 43 .…”
Section: Research Backgroundmentioning
confidence: 99%
“…The safety factor is highly important because, as the existing research has shown, many safety-related accidents occur on the sites where the oil and gas rigs are operational (Kuang et al 2021 ). The risk factors depend entirely on operational process efficiency because, ultimately, there is always a need for an effective working method to bring sustainability to a higher level while increasing product life cycle efficiency (Mehta et al 2021 ; Ibrahim et al 2022 ). The day-to-day operations in the operational phase of an oil and gas project have the major objective of producing more oil and gas so that the clients can be satisfied.…”
Section: Research Article Citation Trendmentioning
confidence: 99%
“…The hydrocarbon potential assessment through the well-logging evaluation of MOF, Pakistan, is the major goal of this research. Determination of the physical characteristics of the rocks is carried out by the well-known approach of formation evaluation. , The specific aims of the well-log evaluation are to determine the presence or lack of commercial hydrocarbon quantities in wellbore formations and to identify small amounts of hydrocarbons that are nonetheless very relevant from an exploration point of view. Wireline log analysis techniques are generally aimed to stimulate primary log data into the approximate quantities of petroleum and water throughout the formation. Physical rock characteristics, which include the pore geometry, lithology, porosity, and permeability, are clarified using geophysical logs. The fundamental objective of the petrophysical analysis is the transformation of log data into petrophysical properties, including porosity, permeability, shale volume, water saturation, and possible hydrocarbon saturation. ,, Determining the correct petrophysical properties for a hydrocarbon deposit is very important for all results, including lithofacies identification, evaluation of the pay zone, hydrocarbon volume estimation, and geophysically interpreting the reservoir. …”
Section: Introductionmentioning
confidence: 99%
“… 4 8 Wireline log analysis techniques are generally aimed to stimulate primary log data into the approximate quantities of petroleum and water throughout the formation. 9 12 Physical rock characteristics, which include the pore geometry, lithology, porosity, and permeability, are clarified using geophysical logs. 13 − 16 The fundamental objective of the petrophysical analysis is the transformation of log data into petrophysical properties, including porosity, permeability, shale volume, water saturation, and possible hydrocarbon saturation.…”
Section: Introductionmentioning
confidence: 99%